(untitled) (Journal of Universal Science Research, 2023)
Currently, the problem of improving the environment state, preserving natural resources are priority and urgent. Human activity is acquiring the global processes scale, which has led to the dangerous regions, separate zones creation with a tense environmental situation, human health deterioration, causing significant damage to nature.[1] The environmental factors impact result of various nature (chemical, physical, biological) and character (social, economic, natural and climatic) is an increase in mortality, morbidity, deterioration in physical development and an increase in the number of people with prepathological conditions[2]. Numerous studies, the population health state in connection with the various factors influence, which were carried out in our country and abroad, have convincingly proved that environment pollution and living conditions adversely affects the population health[3]. Health as the main indicator reflecting the humanity ability to most effectively carry out its social and biological function in certain conditions of a particular region is widely used in scientific research [4].The study of environmental factors influence on the structure, health indicators level and dynamics makes it possible to identify "ecologically conditioned" deviations of these indicators and to carry out zoning of territories according to the environmental comfort degree.Therefore, in order to develop rational tactical decisions aimed at improving health and reducing morbidity and mortality in the Republic of Karakalpakstan, it is necessary to study in detail the factors that determine and shape health in modern conditions, and ways to prevent them.